A MULTI-OBJECTIVE MODEL FOR TIME-COST-QUALITY-RISK TRADE-OFF PROBLEMS IN PROJECT MANAGEMENT - Avsar, Melis Mine Sener; Onut, Semih (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2022)
This study presents a weighted four-dimensional time-cost-quality-risk trade-off problem to assist decision-makers in planning the best possible use of resources. The proposed model aims to minimize time and cost while maximizing quality and safety and to ensure that the project is completed as required. The critical path method was used to calculate the completion time, the analytical hierarchy process method was used to determine the weights of the quality parameters, and the 3T risk assessment method was used to calculate the risk values. The algorithm was coded in GAMS and optimized using CPLEX. A construction project with a deadline of 310 days, a budget of 5,250,000 (sic), 88% quality and a safety index (SI) of 77% was selected to analyze the accuracy of the model. The model achieved a solution with a completion time of 310 days, costs amounting to 5,247,775 (sic), 88.036% quality, and 77.338% SI.
Keywords: Multi-Objective Model; Trade-Off; Weighted Goal Programming; Analytic Hierarchy Process; 3T Risk Assessment; PARTICLE SWARM OPTIMIZATION; CRITICAL-PATH; Engineering